Vortex Simulation of the Bubbly Flow around a Hydrofoil - Tomomi Uchiyama; Tomohiro Degawa (International Journal of Rotating Machinery)
This study is concerned with the two-dimensional simulation for an air-water bubbly flow around a hydrofoil. The vortex method, proposed by the authors for gas-liquid two-phase free turbulent flow in a prior paper, is applied for the simulation. The liquid vorticity field is discrerized by vortex elements, and the behavior of vortex element and the bubble motion are simultaneously computed by the Lagrangian approach. The effect of bubble motion on the liquid flow is taken into account through the change in the strength of vortex element. The bubbly flow around a hydrofoil of NACA4412 with a chord length 100 mm is simulated. The Reynolds number is 2.5×105, the bubble diameter is 1 mm, and the volumetric flow ratio of bubble to whole fluid is 0.048. It is confirmed that the simulated distributions of air volume fraction and pressure agree well with the trend of the measurement and that the effect of angle of attack on the flow is favorably analyzed. These demonstrate that the vortex method is applicable to the bubbly flow analysis around a hydrofoil.